Thirty Years of Mungbean Genome Research: Where Do We Stand and What Have We Learned? - Somta, Prakit; Laosatit, Kularb; Yuan, Xingxing; Chen, Xin (Frontiers in Plant Science, 2022)
Mungbean is a socioeconomically important legume crop in Asia that is currently in high demand by consumers and industries both as dried beans and in plant-based protein foods. Marker-assisted and genomics-assisted breeding are promising approaches to efficiently and rapidly develop new cultivars with improved yield, quality, and resistance to biotic and abiotic stresses. Although mungbean was at the forefront of research at the dawn of the plant genomics era 30 years ago, the crop is a “slow runner” in genome research due to limited genomic resources, especially DNA markers. Significant progress in mungbean genome research was achieved only within the last 10 years, notably after the release of the VC1973A draft reference genome constructed using next-generation sequencing technology, which enabled fast and efficient DNA marker development, gene mapping, and identification of candidate genes for complex traits. Resistance to biotic stresses has dominated mungbean genome research to date; however, research is on the rise. In this study, we provide an overview of the past progress and current status of mungbean genomics research. We also discuss and evaluate some research results to provide a better understanding of mungbean genomics.